Resistance level of several soybean lines of M6 generation to stem rot disease Athelia rolfsii (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Hanafiah DS, Safni I, Siregar LAM, Famanik RIM, Lestmi A, Matondang M. 2020. Resistance level of several soybean lines of M6 generation to stem rot disease Athelia rolfsii. Biodiversitas 21: 4537-4542.  Athelia rolfsii (Curzi) C.C. Tu & Kimbr. is a soil-borne pathogen that causes stem rot disease on plants. The attack is one of the causes of low soybean productivity hence induction of plant resistance is needed to overcome these problems. Mutagenesis is one of the breeding techniques for inducing genetic variability especially for disease-resistant characters in soybean. This research aimed to obtain selected soybean plant lines (Glycine max L. Merr) of M6 generation based on resistant character against stem rot disease A. rolfsii. This research was conducted at the Laboratory of Plant Disease and research field of Faculty of Agriculture, Universitas Sumatera Utara, Medan, Indonesia and soybean planting was carried out on agricultural field, Universitas Sumatera Utara from March to September 2018. This research used augmented design. The treatments were 8 mutant genotypes derived from radiation mutagenesis, that is; Anjasmoro, Argomulyo, and Kipas Putih varieties.  The results showed that the analysis of resistant levels on M6 generation based on disease incidence resulted in 2 lines with resistant criteria to stem rot disease A. rolfsii, that is; M100A25 (5/3) and M200A11 (32/3). Observation of intensity of disease attacks showed that Anjasmoro, Argomulyo, M100A6 (31/1), and M200A12 (6/5) had the lowest resistance level compared to other genotypes. The mutant lines that had high category level of resistance are candidates for resistance lines against stem rot disease A. rolfsii.
Keywords: Athelia rolfsii, M6 generation, resistant, soybean, stem rot disease